Epigenetic Modifications during Angiosperm Gametogenesis - Migicovsky, Zoe D.; Kovalchuk, Igor (Frontiers in Plant Science, 2012)
Angiosperms do not contain a distinct germline, but rather develop gametes from gametophyte initials that undergo cell division. These gametes contain cells that give rise to an endosperm and the embryo. DNA methylation is decreased in the vegetative nucleus (VN) and central cell nucleus (CCN) resulting in expression of transposable elements (TEs). It is thought that the siRNAs produced in response to TE expression are able to travel to the sperm cells and egg cells from VN and CCN, respectively, in order to enforce silencing there. Plant gene imprinting occurs as a result of the difference in TE expression between paternal (silent) and maternal (expressed) genomes in the endosperm. Demethylation during gametogenesis helps ensure that even newly integrated TEs are expressed and therefore silenced by the resulting siRNA production. A final form of epigenetic control is modification of histones, which includes accumulation of the H3 variant HTR10 in mature sperm that is then completely replaced following fertilization. In females, the histone isoforms present in the egg cell and CCN differ, potentially helping to differentiate the two components during gametogenesis. The histone dimorphism between cells is eliminated in both males and females following fertilization, likely preventing these newly acquired epigenetic marks from being transmitted to progeny.